Las lagrimas de la matrioska - Ortiz de Zarate, Marisol; Suarez, Marina (Barcelona : Bambu Editorial, 2014)
A girl describes in her journal her trip to Kiev with her older sister, Marimbo, who wants to become a trapeze artist, and how a boy called Olek passes them a plea for help hidden in a set of nesting matrioska dolls.
In Spanish.
Keywords: Sisters -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Diaries -- Juvenile fiction; Sisters -- Fiction; Adventure and adventurers -- Fiction; Diaries -- Fiction; Kiev (Ukraine) -- Juvenile fiction; Kiev (Ukraine) -- Fiction; Spanish language materials; Spanish language materials; Materiales en espanol